PEMBELAJARAN MENULIS TEKS NEGOSIASI MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH DI SMA - Hasnah, Sitti; Jufri, Jufri (Universitas Negeri Makassar, 2015)
This research is a class action (classroom action research). This study is the subject of Indonesian teachers and students of class X MIA-2 SMAN 7 Makassar academic year 2014/2015. The results showed that the process of implementation of learning activities of teachers and students in the first cycle is not maximized. Based on observations activity of teachers and learners categorized good enough. Implementation of learning in the second cycle of activity of teachers and students has increased with good and excellent categories. Results of the assessment of writing skills negotiating text in the form of a letter of offer and letters of orders increased at the end of the lesson.